KELAYAKAN USAHATANI KEDELAI DI LAHAN DARAT DAN LAHAN SAWAH - Rian Kurnia; Trisna Insan Noor; Eliana Wulandari; Meddy Rachmadi (Universitas Galuh Ciamis, 2019)
This study aims to determine the feasibility of Soybean farming in dryland and paddy fields land in the Jatiwaras Subdistrict, Tasikmalaya Regency. The method used in this study is the survey method, while the data used consists of primary data and secondary data. Determination of sample farmers using the multistage cluster random sampling method. The number of respondents was taken as many as 36 farmers who were divided by farmers on 21 farmers on dryland and 15 farmers on wetland. The results of this study indicate that soybean farming in dryland is more feasible to cultivate with a value of R/C 1.98 while the value of R / C in wetland is 1.62.